Implementasi Green Constitution Demi Mewujudkan Kehidupan Sehat dan Sejahtera - Latipah Nasution (UIN Syarif Hidayatullah Jakarta, 2019)
Abstract:The obligation of every human being is to keep the environment green. Healthy humans are people who value their environment. The Constitution of the Republic of Indonesia has stipulated in Article 28h paragraph (1) that